PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA UPT PUSKESMAS KOTABARU KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Silfia Ella; Hendrian Susi; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
His study aims to determine the effect of workload and work environment onemployee performance at UPT Puskesmas Kotabaru, Keritang District, IndragiriHilir Regency. The population in this study includes all employees with the statusof Civil Servants (PNS) at the UPT Puskesmas Kotabaru, totaling 55 people.Primary data was collected by using a questionnaire as an instrument to provethe results of the study, to test the hypothesis in this study using multiple linearregression analysis with the help of the SPSS program. The sampling techniquethat has been selected is Proposive Sampling (55 employees who are civilservants at the UPT Puskesmas Kotabaru, Keritang District, Indragiri HilirRegency). The results showed that: 1) there was a positive and significant effect ofworkload on employee performance at the UPT Puskesmas Kotabaru, KeritangDistrict, Indragiri Hilir Regency, 2) there was a positive and significant influenceon the work environment on employee performance at the UPT PuskesmasKotabaru, Keritang District, Indragiri Hilir Regency. , 3) workload and workenvironment together have a positive and significant effect on employeeperformance at the UPT Puskesmas Kotabaru, Keritang District, Indragiri HilirRegency. The amount of the influence is 54.4% while the rest is influenced byother variables that are not included in this study. Keywords: Workload, Work Environment, Performance